Infographic: AMSSM position statement on cardiovascular preparticipation screening in athletes: Current evidence, knowledge gaps, recommendations and future directions. Issue 3 (4th October 2016) - Drezner, Jonathan A; O'Connor, Francis G; Harmon, Kimberly G; Fields, Karl B; Asplund, Chad A; Asif, Irfan M; Price, David E; Dimeff, Robert J; Bernhardt, David T; Roberts, William O
Abstract :